Detection of the K99 antigen by means of agglutination and immunoelectrophoresis in Escherichia coli isolates from calves and its correlation with entertoxigenicity. - Guinée, P A (1976)
The common antigen of calf enterotoxigenic strains of Escherichia coli, recently established as the K99 antigen, was studied by means of the slide agglutination test and immunoelectrophoresis. Specific antisera were obtained by absorption of crude antisera with ultrasonicates of autologous cells grown at 18C or by injection into rabbits of the purifies K99 antigen obtained by preparative electrophoresis. The K99 antigen was usually undetectable in calf enterotoxigenic E. coli cultures with capsular K antigens of the A variety grown at 37C on commercially available nutrient agar plates designed for the isolation of Enterobacteriaceae, but was rapidly detectable when grown on a buffered semi-synthetic medium at pH 7.5 (Minca medium). An alternative procedure for the isolation and identification of calf entertosigenic E. coli strains from feces, using the Minca medium, is proposed. K99 was found in 70 of 74 strains of E. coli, the enterotixigenicity of which was established in the ligated gut test in calves. None of the 20 cultures negative in the ligated gut test possessed K99 antigen. The K99 antigen is therefore probably a useful diagnostic tool for the identification of calf enterotixigenic E. coli strains, taking into account that K99 and enterotoxigenicity are controlled by different plasmids.